Become a mega-producer real estate agent - Robert L. Herd (Thomson/South-Western, 2005)
This exciting new addition to Bob Herd's Mega-Producer Series will help real estate agents become even more successful by using a licensed real estate assistant. RESPA (Real Estate Settlement Procedures Act of 1974) and other consumer-related disclosure requirements are increasing at a frantic pace, and requiring overwhelming amounts of paperwork and record-keeping for real estate agents and loan officers. The time spent on these activities can have a negative effect on the income and lifestyle of a highlyproductive real estate agent or loan officer